Trends, distribution, and impact factors of carbon footprints of main grains production in China. (1st January 2021) - Tian, Peipei; Li, Dan; Lu, Hongwei; Feng, Sansan; Nie, Qianwen
Abstract: China is the largest emitter of greenhouse gas (GHG) and has the largest agriculture production in the world, and thus, fully understanding the country's agricultural GHG emissions is of considerable importance. This study evaluates the critical processes, patterns, and impact factors of the carbon footprint of grain production in China based on a new scale data set: agricultural statistics data of over 300 prefecture-level regions. Results show that fertilizer application, straw burning, and methane emissions in rice paddy are the main causes of GHG emissions. High production carbon footprint (PCF) typically appears in areas with low crop yield, whereas low PCF appears in areas with intensive production. Longitude, altitude, and per unit yield are significant correlated with the methane emissions in rice paddy. The increase in GHG emissions from fertilizer application on per unit crop yield highly contributes to the increase in PCF. Moreover, longitude, latitude, and soil properties are the most important factors in PCF variation. Promoting large-scale and intensive modern agriculture production remains a key measure to mitigate GHG emission. Findings can improve the understanding of China's agricultural GHG emissions and subsequently be translated into management suggestions for GHG mitigation. Highlights: Patterns and impact factors of CFs of grains production in China are discussed based on a new scale data set. High PCF typically appears in areas with low crop yield, whereas low PCF appears in areas with large-scale production. GHG emissions from fertilizer application in per unit crop yield highly contributes to the increase in PCF. Longitude, latitude, and soil properties are the most important factors to PCF variation.